EFEKTIVITAS PROMOSI ONLINE, LAYANAN PURNA JUAL DAN PERSEPSI HARGA UNTUK MENINGKATKAN PENGAMBILAN KEPUTUSAN PADA M-COMMERCE - Tegowati Tegowati; Dewi Mutmainnah; Nenny Syahrenny; In’am Widiarma (STIE Mahardhika, 2023)
The purpose of this study is to investigate how pricing perception, after-sales service, and online promotion influence online purchasing decisions. The sample is 150 respondents who have made online purchases via smartphones. Multiple linear regression was employed in the data analysis with SPSS 20.0. The conclusions in this study are as follows: 1) Perception of price affects online purchasing decisions; 2) After-sales service does not affect online purchasing decisions; 3) Online Promotion affects online purchasing decisions. Price perceptions and online promotions affect online purchasing decisions because prices are sensitive, especially for mothers or women. Consumers are rational economic actors. This means that they will take decisions or actions that are most beneficial to them, in this case, related to the price of goods. The law of supply and demand concerns price and quantity. If prices fall, the need for goods and services will increase, and vice versa